Natriuretic Peptides and Blood Pressure Homeostasis: Implications for MANP, a Novel Guanylyl Cyclase a Receptor Activator for Hypertension - Cannone, Valentina; Burnett, John C. (Frontiers in Physiology, 2022)
The heart serves as an endocrine organ producing the hormones atrial natriuretic peptide (ANP) and b-type natriuretic peptide (BNP) which via the guanylyl cyclase A receptor and the second messenger cGMP participate in blood pressure homeostasis under physiologic conditions. Genetic models of the ANP gene or the GCA receptor together with genomic medicine have solidified the concept that both cardiac hormones are fundamental for blood pressure homeostasis and when deficient or disrupted they may contribute to human hypertension. Advances in peptide engineering have led to novel peptide therapeutics including the ANP-analog MANP for human hypertension. Most importantly a first in human study of MANP in essential hypertension has demonstrated its unique properties of aldosterone suppression and blood pressure reduction. Physiology and pharmacology ultimately lead us to innovative peptide-based therapeutics to reduce the burden of cardiovascular disease.